Cold Promoted Activation of Factor VII - Gjønnæss, H (Thrombosis and Haemostasis, 1972)
The cold promoted shortening of the thrombotest times induced by incubation of plasma with prekallikrein activators for 20 hours at 0° C is due to activation of factor VII. No change was recorded for the other coagulation factors. The activation was strong, as the presence of 1 per cent cold activated factor VII reduced the thrombotest time of factor VII deficient plasma from 115 to 38.7 seconds.The activation of factor X by the cold activated factor VII occurred in the course of seconds, in the presence of calcium and thromboplastin. Cold promoted activation of factor VII also implied reduced cephalin time, probably via traces of thrombin inducing intrinsic factor X activator activity during the clotting test.Generation of cold promoted activator activity (CPA) was independent of coagulation factors V, VIII, IX, X, XI, and calcium, but factor XII was a prerequisite. Of factor VII even traces were sufficient for the generation of CPA. The activation of the kallikrein system, that occurs in parallel with the cold promoted activation of factor VII, occurred both in factor VII deficient plasma and in ordinary control plasma. In the reaction sequence, the activation of factor VII therefore is less likely to be the first step, it possibly is a result of activation of the kallikrein system.